Application of ultraviolet light-emitting diodes (UV-LEDs) for water disinfection: A review - Song, Kai; Mohseni, Madjid; Taghipour, Fariborz (Water research (Oxford), 2016)
Ultraviolet (UV) disinfection is an effective technology for the inactivation of pathogens in water and is of growing interest for industrial application. A new UV source — ultraviolet light-emitting diode (UV-LED) — has emerged in the past decade with a number of advantages compared to traditional UV mercury lamps. This promising alternative raises great interest in the research on application of UV-LEDs for water treatment. Studies on UV-LED water disinfection have increased during the past few years. This article presents a comprehensive review of recent studies on UV-LEDs with various wavelengths for the inactivation of different microorganisms. Many inconsistent and incomparable data were found from published studies, which underscores the importance of establishing a standard protocol for studying UV-LED inactivation of microorganisms. Different UV sensitivities to UV-LEDs and traditional UV lamps were observed in the literature for some microorganisms, which requires further investigation for a better understanding of microorganism response to UV-LEDs. The unique aspects of UV-LEDs improve inactivation effectiveness by applying LED special features, such as multiple wavelengths and pulsed illumination; however, more studies are needed to investigate the influencing factors and mechanisms. The special features of UV-LEDs offer the flexibility of novel reactor designs for a broad application of UV-LED reactors. [Display omitted] •The recent studies on newly emerging UV-LEDs for water disinfection are reviewed.•The inactivation effectiveness of different UV-LED wavelengths is illustrated.•The effects of UV-LED multiple wavelengths and pulsed illuminations are presented.•Mechanisms of microorganism inactivation by UV-LEDs are discussed.•Future research directions for UV-LED water disinfection are proposed.